DIAMETERS OF SEMI-IDEAL BASED ZERO-DIVISOR GRAPHS FOR FINITE DIRECT PRODUCT OF POSETS - Porselvi, K.; Elavarasan, B. (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper, we characterize the diameter of zero-divisor graph for direct product P1 × P2 × ... × Pn with respect to direct product I1 × I2 × ... × In, where I1, I2, …, In are semi-ideals of posets P1, P2, ..., Pn, respectively.